Inaccurate Use of Honorifics in Indonesian Language in Communication between Students and Lecturers - Dhea Puspita Anggrainy; Sigit Haryanto (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims investigated the inaccurate use of politeness and honorific Indonesian in oral and written communication between students and lecturers. Methodology: The data source focuses on the use of polite and disrespectful sentences in communicating with lecturers via whatsapp or talking directly. Which explains how students can distinguish polite or disrespectful sentences in communication with lecturers. The Data was collected using classroom observation and the distribution of questions regarding politeness or impoliteness in sentences provided online using WhatsApp. By using polite and disrespectful sentences in questions, students are required to provide a reason why they choose the answer. Results: The first results show that the factors of strength (P), distance (D), and placement position (R) strongly influence the interaction in the classroom between lecturers and student. This is reflected in the choice of greeting, politeness style, and speaking style. The second finding, a survey of students, showed that 85-86% of respondents refused to use "Saudara (you)" to teachers because it was considered rude, and 27-32% began to perceive "Anda (you)" as a form of disrespect. Applications/Originality/Value: The total number of words in the abstract should not exceed 250 words. The findings of this study can help students understand the importance of politeness in academic communication and help lecturers understand the changes in communication patterns occurring among the younger generation.